2022
DOI: 10.3390/healthcare10112157
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness Analysis of Gamiguibi-Tang versus Hwangryunhaedok-Tang for Patients with Insomnia Disorder Based on a Randomized Controlled Trial

Abstract: (1) Insomnia is associated with poor quality of life and loss of productivity, and is a significant economic burden on society. Gamiguibi-tang (GGBT) is the most frequently prescribed herbal medicine for insomnia treatment. Hwangryunhaedok-tang (HHT) is used as an insured herbal medicine for insomnia in the Korean National Health Insurance (NHI) system. This study aims to evaluate the cost-effectiveness of GGBT versus HHT in patients with insomnia disorders based on clinical trial data; (2) Methods: The EuroQo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In assessments of insomnia interventions, 16 studies were CUAs [ 35 , 92 102 ], one reported a CEA [ 101 ], and another combined a CEA and a cost-benefit analysis [ 96 ]. Economic evaluations were most frequently conducted alongside a randomised controlled trial ( n = 30) [ 35 , 54 , 55 , 57 62 , 66 , 82 93 , 95 97 , 99 103 ]. One retrospective case-crossover [ 64 ] and one cohort study [ 63 ] ran economic evaluations concurrently.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In assessments of insomnia interventions, 16 studies were CUAs [ 35 , 92 102 ], one reported a CEA [ 101 ], and another combined a CEA and a cost-benefit analysis [ 96 ]. Economic evaluations were most frequently conducted alongside a randomised controlled trial ( n = 30) [ 35 , 54 , 55 , 57 62 , 66 , 82 93 , 95 97 , 99 103 ]. One retrospective case-crossover [ 64 ] and one cohort study [ 63 ] ran economic evaluations concurrently.…”
Section: Resultsmentioning
confidence: 99%
“…Japan [ 76 , 92 , 104 , 105 ] and Canada [ 68 , 77 , 80 , 101 ] each had four studies, The Netherlands had three studies [ 59 , 95 , 99 ], and Germany [ 96 , 102 ] and France [ 69 , 85 ] had two studies each. Single studies were conducted in Colombia [ 67 ], New Zealand [ 107 ], South Korea [ 103 ], Finland [ 63 ], Australia [ 84 ] and Hong Kong [ 91 ]. Most studies ( n = 28) were conducted in clinical settings, 25 in community settings, and one in a workplace environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations